Modelling and optimization of green pellets classification on roller screens using the discrete element method - Silva, Benito Barbabela e (2017)
The present work studies the classification of green pellets in roller screens using the Discrete Element Method. For this, the individual and bulk properties of the green pellets are determined in physical tests for calibration and validation by comparison with industrial data of contact models that reproduce with verisimilitude the movement of these solids. According to the results, the JKR model was the one that best fitted the interactions of low resistance moist pellets among themselves and rolls surface. Exploratory simulations evaluated the sensitivity of the model to different operating conditions. The application of the methodology of design and analysis of experiments made possible the understanding of the main process control variables amplitude of influence. Based on the results, optimization proposals were elaborated and simulated indicating positive perspectives. The double deck screen in operation and a new segregator double deck design were tested. The results for the new proposal have shown to be promising: better efficiency and higher voidage fraction of the bed of pellets in the grid car.